Characterization of alluvial soil hydrodynamics in the upper Ipanema river basin using the Beerkan method - Antonio Gebson Pinheiro; Alexandre Maniçoba da Rosa Ferraz Jardim; Abelardo Antônio de Assunção Montenegro; Thieres George Freire da Silva; José Raliuson Inácio Silva (Dyna, 2021)
The objective was to model the spatial distribution of the physical properties of the soil through geostatistics in the Brazilian semi-arid region. The study was carried out in the Experimental Basin of Ipanema River, Pernambuco, in an alluvial area with regular grid and samples of 40 points. Infiltration tests were carried out to assess hydraulic conductivity and sampling was performed to determine soil texture and soil organic carbon (SOC). The variables were subjected to descriptive and correlation statistical analyses, in addition to the geostatistical report, which indicated high variability for the hydraulic conductivity of the soil. The best fits were obtained with the Spherical model for the hydraulic conductivity, sand, silt, and clay variables, and the Gaussian model for SOC. Thus, with the geostatistics technique, it was possible to map and verify the main physical characteristics of the soil in the area, providing greater optimization in agricultural planning